Bioremediation of polluted soil due to tsunami by using recycled waste glass - M. Azizul Moqsud (Nature Portfolio, 2021)
Abstract In this research, bioremediation of tsunami-affected polluted soil has been conducted by using collective microorganisms and recycled waste glass. The Tohoku earthquake, which was a mega earthquake in Japan triggered a huge tsunami on March 11th, 2011 that caused immeasurable damage to the geo-environmental conditions by polluting the soil with heavy metals and excessive salt content. Traditional methods to clean this polluted soil was not possible due to the excess cost and efforts. Laboratory experiments were conducted to examine the capability of bioremediation of saline soil by using recycled waste glass. Different collective microorganisms which were incubated inside the laboratory were used. The electrical conductivity (EC) was measured at different specified depths. It was noticed that the electrical conductivity decreased with the assist of the microbial metabolisms significantly. Collective microorganisms (CM2) were the highly capable to reduce salinity (up to 75%) while using recycled waste glass as their habitat.